Administration transfigured: a new administrative paradigm? - Belloubet - Frier Nicole; Timisit Gerard
Administration is changing. Fifteen years ago research in to the new administrative paradiigms sketched the outline, delineated the contours of an administrative machine whose structure, lines and functions were radically different from the image which had long been held of it: an administratiion whose hallmarks were instrumentality, unity and rationality-the three features common to all bodies of doctrine which had heretofore considered the problem of the state and its government. But the modern administration is no longer instrumental but autonomous, no longer unitary and monoliithic but heterogeneous and segmented, no longer rational but conflict driven, shot through with opposing and divergent lines and pol
Keywords: Public Administration